Proposal for simultaneous analysis of fluorescence intensity fluctuations and resonance energy transfer (IFRET) measurements. (29th June 2020) - Stoneman, Michael R; Biener, Gabriel; Raicu, Valerică
Abstract: Resonance energy transfer (RET) and fluorescence fluctuation spectroscopies (FFS) are powerful fluorescence-based techniques for quantifying the self-association of membrane receptors within oligomeric complexes in living cells. However, RET spectrometry's ability to extract information on the detailed quaternary structure of oligomers sometimes rests on assumptions regarding the relative abundances of oligomers of different sizes, while FFS techniques may provide oligomer size information but not quaternary structure details, as they lack a probe for inter-molecular distances. In this report, we introduce a method which we termed 'intensity fluctuations and resonance energy transfer' (IFRET), which combines analysis of donor and acceptor intensity fluctuations with RET efficiency determination. Because the three measured quantities each have a unique dependence on the acceptor mole fraction ( X A ), simultaneous global fitting of all three dramatically reduces ambiguity in the data fitting and choice of the most appropriate fitting model. We demonstrate the effectiveness of the method on simulated brightness and RET efficiency data incorporating mixtures of monomers, dimers, and tetramers and show that IFRET analysis provides a major improvement in both identifying the correct quaternary structure model and extracting the relative abundances of the monomers, dimers, and tetramers. Conceivably, the enhanced resolution of IFRET could potentially provide insight into the functional significance of receptor oligomerization in the presence and absence of cognate ligands.